Challenges of post-conflict urban transportation reconstruction in Mogadishu, Somalia - Ali Mohamed, Abdullahi; Billa, Lawal; Putra Jaya, Ramadhansyah (Elsevier Ltd., 2023)
Mogadishu has experienced continuous internal conflicts in the past two decades, which has destroyed most parts of the city. As a result, it faces daunting development challenges to overcome the legacy of the sustained conflicts and fragility. The capital city, Mogadishu, is a significant pillar in building statehood as it forms an integral part of the growth and development of the country. It essentially provides an environment for the revival of socio-cultural activities and economic productivity in post-civil war reconstruction. Urban sprawls from the influx of displaced populations have extended city and town limits in Somalia, and the capital city Mogadishu bears the blunt of this expansion. Urban transportation in Mogadishu is a significant challenge requiring critical attention. Massive investment in urban transportation infrastructure and networks is vital for the city's urban recovery and economic development. However, the literature shows the lack of information and relevant statistics to support transport planning. Many NGOs (non-governmental organisations) and international development agencies are currently conducting surveys to improve the data resource for the post-conflict planning, development and management of the city. This paper evaluates the urban transportation in Mogadishu by providing an assessment of the challenges and opportunities for the new Mogadishu City Transport Planning Approach (MCTPA). The paper's findings could serve as a template for reconstructing the other urban transport systems in other parts of the country.